Analysis of the Behaviour of Futures Trading in NYMEX (1986-2010) with Regard to Varations in the Level and Volatility of Crude Oil Prices - Atefeh Taklif (فصلنامه پژوهش‌های اقتصادی ایران, 2011)
This paper examines the relationship between the volatility of WTI prices and the open interest volumes (OIV) in NYMEX using a VAR model for the period 1986-2010.  The results from the estimated model imply the existence of a causal relationship from OIV to the price volatility of WTI.  Based on the results obtained from VECM, the existence of a causal relationship between the level of WTI prices and OIV is not confirmed.  This can be justified on the basis that traders’ expectations would primarily affect variations in the futures prices. Since the increase in crude oil price volatilities usually indicates an upward shift in the uncertainties of price forecasts, our results show that the volume of open interest can be regarded as a key factor in the analysis of price behavior in the global oil market.